Induction of callus and expression of compounds in capsicum frutescens supplemented with 2, 4-D - Yaacob, J.S. (2015)

(untitled)
Cili padi" or Capsicumfrutescens is one of many capsicum species from the nightshade family; Solanaceae. It is famous in Malaysia and is widely used as a food ingredient. The bright colours of Capsicwn varieties are due to a combination of esters of capsanthin, capsorubin, zeaxanthinc, cl)1Oxantbinc and other carotenoids. These cxtrlctablc colours of chilli pepper have been broadly used in Jbc food processing business 10 produce • wide range of products like sausages and meal producu, as well as for cheeses, butters, wad dressings, condiment mixtures, gelotine desserts and processed foods. Capsicum frusescens also _ vast medicinal properties, fOI example the compound 'capsaicin' boo been reported to provide temponuy relief for post-sutgical .. in and mouth SO<Is caused by radiatioo therapy and cbentothcrapy. The objectives of this study are to determine the most optimum 2,4- Oichlorophenoxyocetic ocid (2,4-0) honnone concen .... tioD for collus induction from stem explants C. frutescens and the effects of different 2,4-D concentrations on cXPJ'sSion of compouods from C frutescens, Seeds of C. /f'lIlescens were germinated on MS media without honnone (MS basal media) to produce aseptic seedlings of this species, which were then used to supply explants for subsequent tissue culture experiments. Stem explants were excised from aseptic seedlings and cultured on MS media supplemented with various concentrations of 2,4-0 (0.1, 0.3 and O.S mgIL) to induce formation of callus. Fresh weight, dry weight and callus growth percentage in 811 samples were recorded. The highest mean of dry weight was observed in MS media supplemented with O.S mg/L 2.4-0, where 0.4499 ± 0.106 g of callus was produced. The highest percentage of callus growth (16.4%) was also observed in cultures supplemented with O.S mg/L 2,4-0. The callus samples were then subjected 10 HPLC-MS 10 evaluate the effect of hormone concentration on expression of bioacuve compounds in the different samples. Results shewed that ca1Teoylferuloylquinic acids were present in III samples, but was most abundant in callus cells supplemented with 0.3 & O.S mgfl 2,4-0. Interestingly, there was an unknown compound observed to be highly expressed in collus cells supplemented with 0.1 mg/L 2,4-D, but its presence was less significant in callus celts supplemented with 0.3 and 0.5 mgIL 2,4-D. Furthermore, there was also • compound identified as octadecadienoic acid. which was uniquely expressed in callus grown with 05 mglL 2,4-0, but absent in callus cells grown with 0.1 and 0.3 mgIL 2,4-0. The results obtained in this study indicated that plant growth regulators played a role in expression of secondary metabolites in plants. The increase or decrease of these growth regulators may have triggered I change in the secondary metabolite biosynthesis pathways, thus causing differential expression of compounds in this plan